Monitoring a Railway Bridge with Distributed Fiber Optic Sensing Using Specially Installed Fibers - Kinzo Kishida; Thein Lin Aung; Ruiyuan Lin (Sensors)
This article explores the use of distributed fiber optic sensing (DFOS) technology in monitoring civil infrastructure, with a concrete example of an elevated railway bridge in Taiwan. The field test utilized multiple strain-sensing fibers attached to a 1 km span of a bullet train railway bridge, which were combined to calculate the 3-dimensional bridge deformation. The installed sensing system and continuous measurements enabled quick safety confirmation after earthquakes of Richter scale 6.4 and 6.8 magnitudes occurred. Finally, the dynamic monitoring of a bullet train using Distributed Acoustic Sensing (DAS) demonstrated the merits of fiber optic sensing for both static and dynamic measurements. The empirical data gathered through this work aid in the evaluation of DFOS technology for structural-monitoring applications.